(untitled) (Eurasian Research Bulletin, 2023)
This article analysis of proverb and aphorism are considered as paremiological units, and paremiological units formed on the basis of professional lexicon are cross-analyzed. Differences and similarities in paremiological units of two peoples are demonstrated on the basis of a factual example